Knowledge, attitude and practice on hand hygiene and factors associated to its practice among healthcare professionals in a pediatric oncology ward, Saudi Arabia - Aldawsari, Mujibah Saleh A. (2022)
Background: Hands are the most common vehicle of pathogen transmission within the healthcare environment. As such, strict hand hygiene is the leading measure for reducing healthcare-associated infections (HCAIs) and preventing the spread of antimicrobial resistance. In addition, these infections are the main cause of morbidity and mortality among children with acute myeloid leukaemia (AML) because of the effect of chemotherapy on immunosuppression. This study is aimed at determining the factors associated with hand hygiene practices among healthcare workers caring for children with leukaemia in a paediatric oncology ward at King Saud hospital in Riyadh, Saudi Arabia. Methods: In this cross-sectional study, a total of 190 medical doctors and nurses were evaluated using a self-administered questionnaire to assess their knowledge, attitude and practices regarding hand hygiene. In addition, information regarding sociodemographic characteristics was collected. A simple random sampling technique was used to select the participants from December 2021 until January 2022. The data were analysed using SPSS version 26 for Microsoft Windows. Descriptive statistics (means, median, standard deviations of continuous variables, as well as frequencies and percentages of categorical variables) were used to summarise the data. A chi-square test was used to determine the association between dependent and independent variables. Results: This study comprised 190 healthcare workers (74.7% nurses and 25.3% medical doctors) with a response rate of 100%. The mean age ±SD was 37.8 ±9.8 years (range 23-83 years). Most of the participants were female (85.8%), Saudis (51.1%) and nurses (74.7%). The majority of the participants had a bachelor's degree (54.7%), followed by postgraduate education (24.2%), and diploma (21.1%). Most of the participants had work experience of 5-15 years (52.1%), followed by those with more than 15 years (25.8%) and less than 5 years (22.1%). Around 54% of participants had good knowledge regarding hand hygiene, 51.6% had a positive attitude regarding hand hygiene, and 55.8% had satisfactory practice of hand hygiene. The education level (p=0.004), healthcare workers' knowledge (p<0.001) and healthcare workers' attitude (p<0.001) were significantly associated with healthcare workers' practice of hand hygiene. Conclusion: This study established that more than 44% of healthcare workers had unsatisfactory hand hygiene practices. In order to ensure better hand hygiene, effective programmes should be designed to increase healthcare workers' awareness regarding the knowledge, attitude and practice of hand hygiene. Strict guidelines must be implemented to regulate nosocomial infection.